Writing revolt : an engagement with African nationalism, 1957-67 - Ranger, T. O. (Woodbridge, Suffolk : James Currey ; Harare, Zimbabwe : Wea ver Press, 2013)
This memoir of the years between 1957, when he first went to Souther n Rhodesia, and 1967 when he published his first book, is both an intim ate record of the African awakening which Ranger witnessed during those ten years, and of the process which led him to write Revolt in Souther n Rhodesia. Intended as both history and as historiography, Writing Rev olt is also about the ways in which politics and history interacted. Th e men with whom Ranger discussed Zimbabwean history were the leaders of African nationalism; his seminar papers were sent to prisons and into restricted areas. Both they and he were making political as well as int ellectual discoveries. The book also includes a brief account of Ranger 's life before he went to Africa.
1. Preface -- 2. 1929-57, a very ordinary boy -- 3. 1957 The Univers ity College of Rhodesia & Nyasaland -- 4. 1958 The Southern Rhodesia Af rican National Congress -- 5. 1959 The Central African Emergencies -- 6 . 1960 The National Democratic Party -- 7. 1961 Citizens Against the Co lour Bar -- 8. 1962 The Zimbabwe African People's Union -- 9. 1963 and afterwards: Deportation, the Nationalist Split, Dar es Salaam and Writi ng Revolt -- Appendix of names -- Select references -- Terence Ranger b ibliography -- Index of names.
Includes bibliographical references (p. 191-203) and index.
Keywords: Ranger, T. O. -- Biography; Zimbabwe African People's Union; Nationalism -- Zimbabwe -- History; Zimbabwe -- Politics and government; Zimbabwe -- Historiography